Pencemaran Lingkungan : Pemahaman dan Penanggulangan Pencemaran (International Forum of Researchers and Lecturers, 2025)
The introduction of toxic substances or energy into the environment degrades environmental quality, which in turn can have negative effects on living things like human health, biodiversity, and the global climate. This multi-faceted problem has far-reaching consequences for ecosystems and human life. For Indonesia, this has grown into a major problem throughout the last several decades. Water, air, soil, and noise pollution have all seen dramatic increases due to the expansion of cities, the industrial sector, and the proliferation of motor vehicles. All four forms of Indonesian environmental pollution—air, water, soil, and noise—are covered in this research, along with their origins, effects on human and environmental health, and potential solutions, both governmental and grassroots. A literature review of secondary sources, such as government papers, scientific journals, and other official publications, is employed as the technique. This document is written with the intention of drawing attention to the significance of environmental protection and offering broad preventative actions. According to the results, industrial operations, automobiles, household garbage, and a general lack of environmental consciousness are the main causes of pollution. Hence, in order to lessen the impact of pollution and enhance environmental quality, technological solutions, regulatory laws, and communities that are both interdisciplinary and collaborative are crucial tools.